Taxonomic novelties and synopsis of the genus Blakea (Melastomataceae, Pyxidantheae) in the Eastern Cordillera, Colombia - Urrea, Johan; Mendoza-Cifuentes, Humberto; García, Néstor (Instituto de Ecología, A.C., 2023)
Background and Aims: Blakea is a Neotropical genus of woody plants with 192 species, of which more than 80 are distributed in Colombia, with high levels of endemism. Despite the high diversity of the genus in the country, few taxonomic studies have been carried out at the regional level, so that knowledge about Blakea is scarce in general. This paper deals with a taxonomic synopsis of the genus for the Eastern Cordillera of Colombia, nomenclatural novelties are proposed, and a new species is described.Methods: More than 200 specimens from different herbaria in Colombia were reviewed; in addition, the prologues and type specimens were consulted online and compiled. The richness and distribution of the genus in the region are established, annotations are made on its phenology, conservation status and a representative specimen per department are cited. Taxonomic comments are also made on some species.Key results: In total, 25 species and one variety were recorded for the study area, one of which was identified at the morphospecies level. A new species is described within the study area (Blakea reflexa), B. clusiifolia is reestablished, B. schlimii is reported for the country and the departmental and elevational distributions of 12 species are expanded.Conclusions: Blakea presents a high richness in the Eastern Cordillera of Colombia, so this area is key for the study and conservation of the group at regional and national levels. It is important to continue with detailed regional taxonomic studies of the genus to precisely know its current status and possible future trends.